Adsorption behavior of mephentermine on the pristine and Si, Al, Ga- doped boron nitride nanosheets: DFT studies - Mahla Mosavi (Journal of Chemistry Letters)
In this research, the adsorption behavior of pristine, Si- and Al- and Ga-doped boron nitride nano sheet are investigated toward mephentermine using density functional theory (DFT) calculations. Total energies, geometry optimizations were obtained and density of state (DOS) analysis was performed at B3LYP level of theory with the 6-31G* basis set. The adsorption energy (Ead) between mephentermine and the pristine, Si- and Al- and Ga doped BNN is changed in the following order: Ga-Complex-N> Al-Complex-N>Si-Complex-N>complex-N. The Ead of the BNN-mephentermine complex is -2.09 kcal/mol, which is low and shows that the adsorption is weak physicaly. The Ead of the Al-doped BNN-mephentermine complex is -34.06 kcal/mol, ΔEg = -1.37%, indicating a low sensitivity of the Al-doped boron nitride nanosheet to the adsorption of mephentermine and is not suitable for sensing. As mentioned, due to the adsorption energy of −34.06 kcal/mol and the rather long recovery time, a strong interaction is not suitable for a sensor. A system with high adsorption energy can be a sensor at high temperatures, because at high temperatures the recovery time is reduced. The Ead of the Ga-doped BNN-mephentermine complex is -46.46 kcal/mol, ΔEg = -6.39%, indicating a low sensitivity of the Ga-doped boron nitride nanosheet to the adsorption of mephentermine. the adsorption energy of -46.46 kcal/mol is not suitable and indicates a long recovery time, As a result, it helps to decompose this compound and remove this compound.